Kirurgiens nytte - Ruud, Lise Camilla (Tidsskrift for kulturforskning, 2015)
In 1736, Theatrum Anatomico-Chirurgicum was established in Copenhagen as part of royal enlightenment effort to provide better surgical services to the Danish-Norwegian population. In 1990, the first laparoscopic cholecystectomi (removal of gallbladder with keyhole surgery) was performed at Gjøvik hospital in Oppland County. Both events are analyzed by foregrounding how surgery's utility was enacted by a multitude of actors, human and non-humans, through different public-scientific practices. An original contri-bution of the article is the use of terminology from Science technology studies and Actor-network theory within history of surgery, and the article seeks to breathe new life into a subject that has formerly been looked at through other analytic lenses.